Examining the Role of Big Data and Block Chain Technology in Advancing High-Quality Development within the Sports Industry’s Digital Economy - Yahan Yang; Yizhang Gong; Helai Bai; Zhaoxiang Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
In the ever-evolving landscape of the global economy, big data, the new generation of artificial intelligence, and block chain technology have risen as pivotal drivers of the data economy. These technologies are playing an increasingly vital role in catalyzing transformative changes within the sports industry and the broader digital economy. As the world economic patterns continue to shift and Internet technologies advance, the digital economy, particularly within the sports sector, faces higher demands and opportunities for innovation. In the context of China's economic development, the digital economy has emerged as a primary pathway to achieving high-quality economic growth. This paper embarks on a theoretical exploration of the profound impact of big data and blockchain technology within the sports industry, examining their current applications and potential. The research presented here seeks to unravel the intricate mechanisms through which big data and blockchain technology drive high-quality development within the sports sector's digital economy. By shedding light on these dynamics, this paper contributes valuable insights to guide and optimize the future of China's economic development, with a strong emphasis on the sports industry as a critical focal point for innovation and growth.